Effects of Electroacupuncture on Opioid-Induced Constipation in Patients With Cancer: Study Protocol for a Multicenter Randomized Controlled Trial - Wang, Weiming; Wang, Xinlu; Liu, Yan; Sun, Yuanjie; Liu, Xiaoxu; Yan, Yan; Liu, Zhishun (Frontiers in Medicine, 2022)
Background: Opioid-induced constipation (OIC) is one of the most prevalent adverse events associated with cancer patients who receive opioid analgesics for moderate to severe pain. Acupuncture may be an effective treatment for OIC. We designed this trial to assess the efficacy and safety of electroacupuncture for OIC in cancer patients. Methods: This is a multicenter, sham-controlled, parallel-group, subject- and assessor-blinded randomized trial. A total of 100 cancer patients with OIC will be randomly assigned to either the electroacupuncture group or the sham electroacupuncture group at a ratio of 1:1. Patients in each group will receive a total of 24-session treatment over 8 weeks, 3 sessions a week and 30 minutes each session. Thereafter, patients will be followed up for another 8 weeks. The primary outcome will be the proportion of responders, defined as a patient who has at least three spontaneous bowel movements (SBMs) per week and an increase of at least one SBM from baseline in the same week for 6 weeks or more out of the 8-week treatment period. The secondary outcomes will include the mean weekly SBMs and complete spontaneous bowel movements, the mean Bristol Stool Form Scale score for stool consistency, the mean score for straining of SBM, the total and subscale scores of Patient Assessment of Constipation-Symptom questionnaires, and the total and subscale scores of Patient Assessment of Constipation-Quality of Life questionnaire. Patients’ global assessment of treatment effectiveness, patients’ expectation towards the effectiveness of acupuncture and safety of acupuncture will also be assessed. All efficacy analyses will be performed in the intention-to-treat population. Discussion: To improve adherence to intervention protocols, the majority of the participants will be recruited from an inpatient setting. The results will help to determine the clinical effects and safety of electroacupuncture for the treatment of OIC among patients with cancer. Trial registration: ClinicalTrials.gov Identifier: NCT03797586, registered on 4 January 2019. https://clinicaltrials.gov/ct2/show/NCT03797586